SEASONAL AND AGE-RELATED FEATURES OF SPERM PRODUCTION OF BREEDING BULLS-SPERMODONORS OF THE BUSHUEV BREED - Sherali Shamshievich Allayarov (European Science Publishing, 2024)
The studies were conducted on the zebu-like Bushuev bulls, created in Uzbekistan. The Bushuev bulls, due to their high adaptability to the hot climate of Uzbekistan, have higher quantitative and qualitative indicators of sperm productivity throughout the entire period of economic use in local conditions. In comparison with imported bulls, they showed comparative stability of sperm production indicators throughout the year, that is, by seasons of the year, and they also remained longer in the main herd, which means a satisfactory number of sperm doses received during life, despite the relatively small volume of ejaculates. In addition, cryopreserved sperm products of bulls of this breed have a better survival rate than sperm of imported bulls.
Keywords: bull-manufacturer, breed, volume of ejaculate, concentration of sperms, spermodosis.